Effect of limited - creep feeding on performance of spring-born calves - D. Simms; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1988)
Three limited-creep feeding trials were conducted with spring-born suckling calves on native grass. The 1696 crude protein, high energy creep feed containing Bovatec® was fed from mid-August to weaning in mid-October. Limited-creep feeding increased (P<.05) calf gains .19 lb per/head/daily with an average daily consumption of 2.15 lb, giving a creep feed-to-gain conversion rate of 11.2.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen& #x27; s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Creep feeding; Calves; Performance